Dependent Science in Independent Africa - MOROZENSKAYA Evgenia Viktorovna (Ученые записки Института Африки Российской академии наук, 2025)
Review of the book: Sooryamoorthy R. (2023). Independent Africa, Dependent Science: Scientific Research in Africa. Singapore: Palgrave Macmillan. https://doi.org/10.1007/978-981-99-5577-0